Researching internal migration - Rajan, S. Irudaya, author.
1 online resource
Keywords: "Researching Internal Migration is a comprehensive guide for researchers and professionals to study internal migration in developing and underdeveloped economies. This book: - Explains key theoretical concepts related to migration; - Guides students and researchers on how to design surveys and the utility of census data; - Unravels the complexities of large datasets and their interpretation; - Includes techniques for indirect measurement; - Presents methodology of estimating remittances at the sub-national and national level; - Acquaints the impact of migration during emergency situations or pandemics like Covid-19; - Offers perspective and tools for evaluating policy impact of migration. Accessibly written, this book will be an essential theoretical and empirical guide for researchers in development studies, public policy, population studies, human geography, and migration and diaspora studies"--